Studium na temat rozwoju umiejętności studentów matematyki ze specjalnością nauczycielską = A study on capacity development of mathematical pedagogy students - Nguyen, Hau Huu; Hoa, Tuong Anh; Anh, Giang Pham (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents some courses in Bachelor of capacity development of mathematical pedagogy students. Firstly, we analysed Bachelor of Mathematical Education program. Secondly, we conducted a survey to identify Vietnamese students who need to be equipped and experienced some performance capacities. Thirdly, we suggested some solutions to be taken during courses related to the module of teaching methods and pedagogic practice in order to contribute to the promotion of these competencies for students. Finally, we answered the question "How to develop such capacities for students?".
Keywords: zdolność do działania; matematyka pedagoga; nauczanie metod; matematyka; matematyka elementarna; performance capacity; mathematical pedagogics student; method teaching; mathematics; elementary mathematics